Gerak Lompat Ikan Gurami Menggunakan Software Tracker Sebagai Praktikum Konservasi Energi Mekanik - Arina Zaida Ilma; Heru Kuswanto; Adha Hujatulatif (Postgraduate, University of Mataram, 2022)
One of the phenomena of gourami fish is the jumping motion. In analyzing the fish motion, errors are often experienced in observations, tend to be subjective or take a long time. An alternative software to analyze the fish motion is the Tracker software. The study aims to analyze the video of the Gourami fish motion phenomenon using Tracker software in the mechanical energy conservation practicum. This type of research is experimental research. Based on the results, the greater the mass of the fish indicates the greater the kinetic energy and potential energy in the motion of the fish. Kinetic energy depends on the mass and speed of the Gourami fish jumping. While the potential energy depends on the height of the Gourami fish when jumping. It is also affected by the fish's mass and the acceleration of gravity. The video analysis of the motion of the jumping gourami using Tracker can be used in science learning, especially in physics practicum about the law of conservation of mechanical energy